2021
DOI: 10.3354/cr01681
|View full text |Cite
|
Sign up to set email alerts
|

Modelling snowfall in southern Italy: a historical perspective in the Benevento Valley (1645-2018)

Abstract: The lack of long-term, homogeneous snowfall records is a limitation in environmental studies. Statistical modelling holds potential to extend snowfall records back in time with a limited set of predictors: snow severity and winter-spring temperatures (with their variability) to reflect elevation influences. The annual number of snow days (SDY) in the Benevento Valley (southern Italy) was detailed for the period 1870-2018. Calibrated in the period 1870-1968 (R2 = 0.85) and validated in the period 1969-2018 (R2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Fontrodona Bach et al (2018) studied changes in mean and maximum snow cover depths based on observed data in Europe from 1951. Many other papers have analysed different aspects of snow patterns at regional and country scales, for example, in central Europe (Dong and Menzel, 2020), Austria (Olefs et al, 2020), Bulgaria (Brown and Petkova, 2007), Great Britain (Kay, 2016;Brown, 2019), Poland (Szwed et al, 2017;Tomczyk et al, 2021), Italy (Diodato et al, 2021), Slovakia (Siman and Polč ak, 2017;Siman and Sl avkov a, 2019), the Swiss-Austrian Alps (Klein et al, 2016;Schöner et al, 2018), Switzerland (Marty and Blanchet, 2012), and others.…”
Section: Introductionmentioning
confidence: 99%
“…Fontrodona Bach et al (2018) studied changes in mean and maximum snow cover depths based on observed data in Europe from 1951. Many other papers have analysed different aspects of snow patterns at regional and country scales, for example, in central Europe (Dong and Menzel, 2020), Austria (Olefs et al, 2020), Bulgaria (Brown and Petkova, 2007), Great Britain (Kay, 2016;Brown, 2019), Poland (Szwed et al, 2017;Tomczyk et al, 2021), Italy (Diodato et al, 2021), Slovakia (Siman and Polč ak, 2017;Siman and Sl avkov a, 2019), the Swiss-Austrian Alps (Klein et al, 2016;Schöner et al, 2018), Switzerland (Marty and Blanchet, 2012), and others.…”
Section: Introductionmentioning
confidence: 99%